Hydrolytic Stability of Methacrylamide and Methacrylate in Gelatin Methacryloyl and Decoupling of Gelatin Methacrylamide from Gelatin Methacryloyl through Hydrolysis. Issue 18 (16th August 2018) - Zheng, Jing; Zhu, Mengxiang; Ferracci, Gaia; Cho, Nam‐Joon; Lee, Bae Hoon
Abstract: Gelatin methacryloyl (GelMA; GM) is a promising nature‐derived photocurable material that can mimic the extracellular matrix because GelMA features tailorable mechanical properties, proteolytic degradation, and good cell adhesion. GelMA contains not only methacrylamide but also methacrylate. However, the hydrolytic stability of methacrylamide and methacrylate groups of GelMA in aqueous solutions has not been scrutinized. Here, the structural change of GelMA through hydrolysis is investigated for the first time. The structural change of hydrolyzed GelMA is quantitatively identified using colorimetric and 1 H NMR methods. The methacrylate groups decompose markedly at high pH solutions, but the methacrylamide groups remain stable. Further, pure gelatin methacrylamide is successfully decoupled from GelMA for a better understanding of GelMA structure and future use for biomedical applications. Abstract : Structural stability of gelatin methacryloyl containing both methacrylamide and methacrylate groups is investigated through a hydrolysis method. 1 H NMR spectroscopy and colorimetric methods quantified the structural and compositional change of gelatin methacryloyl during the hydrolysis. Pure gelatin methacrylamide is completely decoupled from gelatin methacryloyl for the first time.